Trade Policies in South Asia : An Overview, Volume 1. Operational Summary - World Bank (Washington, DC, 2013)
During the last decade, South Asia's five largest countries - India, Pakistan, Sri Lanka, Bangladesh and Nepal - have been implementing trade policy reforms, gradually moving their economies away from protectionism toward greater trade openness and global economic integration. In the late 1980s and early 1990s, the four mainland countries began to follow the liberalizing course on which Sri Lanka had embarked in the late 1970s. Each country faces differing opportunities to exploit and resistances to overcome. Because many of their circumstances and choices are similar, however, this paper seeks to assess their situations collectively as well as separately. Many of its findings are broadly applicable. So, with allowances for historic, economic and social differences, are many of its policy recommendations. The bulk of the report describes key aspects of the current trade regimes in the Jive largest South Asian states and the policies and practices that have produced the systems now in place. It principally focuses on traditional trade policies which affect imports and exports i.e. tariffs, non-tariff barriers, anti-dumping, export policies, and to a limited extent aspects of sanitary and technical regulations that affect trade. All of these are still major issues of concern and debate in South Asia. The report does not attempt to describe where the South Asian countries stand on newer trade policy issues which are prominent in World Trade Organization negotiations, such as trade in services, intellectual property, government procurement and Customs valuation. The report also does not attempt to place the South Asian countries' trade policies in the context of their trade and other aspects of their economic performance. Its purpose is rather to provide up-to-date information about, and interpretations of, the current trade policies it covers, with the idea that this should provide starting points for further applied economic research on useful and relevant topics, as well as points of reference and factual information for discussion and debate. Nevertheless, the report does assess, on theoretical and empirical grounds, the appropriateness of the policies described. Conclusions and suggestions for change are generally summarized at the end of each stocktaking section. This summary, in condensing the work of stocktaking, highlights the key issues that all or most of the countries have addressed and need to pursue further. To reinforce the operational nature of those findings, the summary deals with the recommendations next, as an immediate continuation of the central policy questions. It then reviews trade policies in three key sectors- agriculture, fertilizers, and textiles and clothing.